2009
DOI: 10.1007/s10517-009-0519-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Serotonin in Systemic Impairment of Motor Function of the Digestive Tract

Abstract: We studied the role of serotonin in systemic impairment of motor function of the digestive tract. Administration of a nitric oxide donor methylene blue into the pre-fundal portion of the stomach and application of a loose ligature to the terminal part of the sigmoid colon were performed after pretreatment with serotonin. Serotonin had a stabilizing effect on esophageal antiperistalsis under conditions of dynamic obstruction of the sigmoid colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Several research studies involving patients with musculoskeletal pain have examined the correlation between these two nosological entities, although more focus has been given to the central nervous system structures involved in pain perception and colonic stimulation [39]. There is no scientific evidence to explain the frequent occurrence of this nosological entity in patients with myofascial pain, although several studies have indicated the occurrence of constipation in patients with musculoskeletal pain [11,40,41]. However, to establish constipation in our study we employed a method subjective evaluation tool (Roma III), but internationally validated and recognized for considering the effort to defecate, frequency and consistency (shape) of feces, classified by Bristol Fecal Shape Scale (EBFF) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies involving patients with musculoskeletal pain have examined the correlation between these two nosological entities, although more focus has been given to the central nervous system structures involved in pain perception and colonic stimulation [39]. There is no scientific evidence to explain the frequent occurrence of this nosological entity in patients with myofascial pain, although several studies have indicated the occurrence of constipation in patients with musculoskeletal pain [11,40,41]. However, to establish constipation in our study we employed a method subjective evaluation tool (Roma III), but internationally validated and recognized for considering the effort to defecate, frequency and consistency (shape) of feces, classified by Bristol Fecal Shape Scale (EBFF) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Outro importante neurotransmissor associado ao processo de transmissão dolorosa é a serotonina (5-HT), amina biogênica que tem sua taxa de síntese dependente da disponibilidade de triptofano livre no plasma. A 5-HT é secretada por diversos neurônios no núcleo da rafe e atua como inibidora das vias de transmissão dolorosa na medula, estando relacionada com as alterações de comportamento, de humor, ansiedade, depressão, sono, fadiga, supressão do apetite, além de estar envolvida na regulação da motilidade do trato gastrointestinal (CAMILLERI, 2006;LYCHKOVA, 2009;RAIMUNDO et al, 2009). Estudos in vivo revelaram que alterações no metabolismo da 5-HT, com a diminuição na sua síntese e liberação, implicam na redução da atividade do sistema inibidor de dor, com uma consequente elevação da resposta dolorosa a estímulos algogênicos (LYCHKOVA, 2009;RAIMUNDO et al, 2009).…”
Section: A Nocicepção Dolorosaunclassified
“…A 5-HT é secretada por diversos neurônios no núcleo da rafe e atua como inibidora das vias de transmissão dolorosa na medula, estando relacionada com as alterações de comportamento, de humor, ansiedade, depressão, sono, fadiga, supressão do apetite, além de estar envolvida na regulação da motilidade do trato gastrointestinal (CAMILLERI, 2006;LYCHKOVA, 2009;RAIMUNDO et al, 2009). Estudos in vivo revelaram que alterações no metabolismo da 5-HT, com a diminuição na sua síntese e liberação, implicam na redução da atividade do sistema inibidor de dor, com uma consequente elevação da resposta dolorosa a estímulos algogênicos (LYCHKOVA, 2009;RAIMUNDO et al, 2009). Evidências científicas provenientes de estudos em modelos animais demonstraram que as citocinas poderiam induzir a dor por diversos mecanismos.…”
Section: A Nocicepção Dolorosaunclassified